Lithium niobateX-cut,Y-cut, andZ-cut surfaces fromab initiotheory - Sanna, Simone; Schmidt, Wolf Gero (Physical Review B)

GaN/LiNbO3 (0001) interface formation calculated from first-principles - Sanna, Simone; Schmidt, Wolf Gero (Applied Surface Science)

Magnetic characterization of conductance electrons in GaN - Scholle, A.; Greulich-Weber, S.; As, Donat Josef; Mietze, Ch.; Son, N. T.; Hemmingsson, C.; Monemar, B.; Janzén, E.; Gerstmann, Uwe; Sanna, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (b))

Chemical reactivity on surfaces: Modeling the imide synthesis from DATP and PTCDA on Au(111) - Rauls, E.; Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Fine Structure of Triplet Centers in Room Temperature Irradiated 6H-SiC - Scholle, Andreas; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
In non-annealed 6H-SiC samples that were electron irradiated at room temperature, a new EPR signal due to a S=1 defect center with exceptionally large zero-field splitting (D = +652•10-4 cm-1) has been observed under illumination. A positive sign of D demonstrates that the spin-orbit contribution to the zero-field splitting exceeds by far that of the spin-spin interaction. A principal axis of the fine structure tilted by 59° against the crystal c-axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin-orbit coup¬ling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

GaN growth on LiNbO3 (0001) - a first-principles simulation - Sanna, Simone; Schmidt, Wolf Gero (physica status solidi (c))

Temperature dependent stability of self-assembled molecular rows - Blankenburg, S.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initio investigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, G. (physica status solidi (c))

Aus dem Deutschen ins Italienische (zusammen mit M. Brusotti, L. Gasperoni und C. Piazzesi): G. Abel, Filosofia dei segni e dell’interpretazione

Nuzzo, Angelica (Ed.), Hegel and the Analytic Tradition, London/New York 2010 - Ficara, Elena (Hegel-Studien)

Negation und die Logik der Philosophie bei Hegel - Ficara, Elena (Nichts, Negation, Nihilismus. Die Europäische Moderne als Erkenntnis und Erfahrung des Nichts)

Due in uno. Che cosa è e che cosa fa l’io che pensa - Ficara, Elena (Filosofia dell’avvenire)

Der ontologische Gottesbeweis bei Hegel und in der Analytischen Philosophie - Ficara, Elena (Gott in der deutschen klassischen Philosophie und im Denken der Gegenwart)

Ursprünge des Ausdrucks ’das Logische’ beim frühen Hegel - Ficara, Elena (Archiv für Begriffsgeschichte)

Immagini della dialettica hegeliana. La croce e la rosa. - Ficara, Elena (Archivio di storia della cultura)

Hegel’s Dialectic in Contemporary Philosophy - Ficara, Elena (Idealistic Studies)

Heidegger e il problema della metafisica - Ficara, Elena

Scalable Multi Phase Interleaved Boundary Mode PFC Concept enabling Energy- and Cost Efficient PSUs in the kW-Range - Schafmeister, Frank; Wang, Xudong; Grote, Tobias; Ide, Peter (Proc. IEEE International Symposium on Industrial Electronics (ISIE))

FPGA-based realization of self-optimizing drive-controllers - Paiz, C.; Hagemeyer, J.; Pohl, C.; Porrmann, M.; Rückert, U.; Schulz, B.; Peters, W.; Böcker, Joachim (2009 35th Annual Conference of IEEE Industrial Electronics)

Optimal energy management for a hybrid energy storage system for electric vehicles based on Stochastic Dynamic Programming - Romaus, Christoph; Gathmann, Kai; Böcker, Joachim (2010 IEEE Vehicle Power and Propulsion Conference)

Efficiency improvement of an IPMSM using Maximum Efficiency operating strategy - Pohlenz, Daniel; Böcker, Joachim (Proceedings of 14th International Power Electronics and Motion Control Conference EPE-PEMC 2010)

Observer for the rotor temperature of IPMSM - Specht, Andreas; Böcker, Joachim (Proceedings of 14th International Power Electronics and Motion Control Conference EPE-PEMC 2010)

Multiobjective search for the management of a hybrid energy storage system - Boxnick, Simon; Klopfer, Stefan; Romaus, Christoph; Klopper, Benjamin (2010 8th IEEE International Conference on Industrial Informatics)

Energy transfer with doubly-excited switched reluctance drive - Schneider, T.; Schulte, C.; Mathapati, S.; Böcker, Joachim (SPEEDAM 2010)

Modeling and Control Design for a Very Low-Frequency High-Voltage Test System - Cao, Z.; Hu, M.; Fröhleke, N.; Böcker, Joachim (IEEE TRANSACTIONS ON POWER ELECTRONICS 25(2))

Optimal Design of Motor and Gear for Drives With High Acceleration by Consideration of Torque–Speed and Torque–Acceleration Product - Grotstollen, Horst (IEEE Transactions on Industry Applications)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

The Ariadne System. A flexible and extensible framework for the modeling and storage of experimental data in the humanities - Menke, Peter; Mehler, Alexander (Proceedings of LREC 2010)

Towards a Simulation Model of Dialogical Alignment - Mehler, Alexander; Weiß, Petra; Menke, Peter; Lücking, Andy (Proceedings of the 8th International Conference on the Evolution of Language (Evolang8))

Rudolf Seising, The Fuzzification of Systems. The Genesis of Fuzzy Set Theory and Its Initial Developments up to the 1970s. Springer: Berlin/Heidelberg 2007 (Studies in Fuzziness and Soft Computing; 216) - Peckhaus, Volker (Isis)

FDM Part Quality Manufactured with ULTEM 9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (Proceedings of International Conference Polymeric Materials)
Generative production techniques have the advantage of manufacturing parts via an additive process without needing a forming tool. One of these additive manufacturing technologies is “Fused Deposition Modeling” (FDM). From a 3D-CAD data set, components and assemblies are manufactured out of thermoplastic material in only a few working steps. Native software automatically slices the data, calculates the support structures, and creates toolpaths. The parts then are built up layer by layer by means of an additive process. An extrusion head deposits the molten thermoplastic filament to create each layer. This technology began as a process for creating prototype parts; recently it has found new utility in the production of manufacturing tools and as a manufacturing process for end-use parts. In order to be used as a part for serial production, the components must possess the required mechanical properties. To this end, not only is the chosen material relevant, but a correct process control is also necessary. An interesting material for the aircraft and automotive industry is the material PEI with the trade name Ultem*9085. This material should typically be used on FDM-machines for the manufacturing of end products. The aim of the research is to determine the present mechanical data based on the process control, as well as reproducibility from job to job. In this work the influence of the orientation and the structure of the manufactured parts based on the mechanical data are analyzed. Sample parts are generated with the given parameters of the native software based upon the CAD data. First, specimens were analyzed concerning their geometry and configuration. The dimensions and weight were measured. The mechanical tests conducted were the tensile and compression tests.

Robert und Hermann Grassmann’s Influence on the History of Formal Logic (Videomitschnitt des Vortrags) - Peckhaus, Volker (International Grassmann Conference. Hermann Grassmann Bicentennial: Potsdam and Szczecin, 16–19 September 2009. Video Recording of the Conference)

Entwurf und Betrieb hybrid-elektrischer Fahrzeugantriebe am Beispiel von Abfallsammelfahrzeugen - Knoke, T.

Wirkungsgradoptimierte Regelung hoch ausgenutzter Permanent-Synchronmaschinen im Antriebsstrang von Automobilen - Meyer, M.

Power Supplies for High-Power Piezoelectric Ultrasonic Motor - Li, R.

Hochschulforscher oder Hochschullehrer? Eine Panel-Daten-Analyse wirtschaftswissenschaftlicher Bachelor- und Masterkurse - Lück, Sonja (Hochschulmanagement)

Portfolioarbeit im fremdsprachlichen Schreibunterricht - Ballweg, Sandra (Grenzen überschreiten: sprachlich – fachlich – kulturell. Dokumentation zum 23. Kongress für Fremdsprachendidaktik der Deutschen Gesellschaft für Fremdsprachenforschung (DGFF). Leipzig, 30. September – 3. Oktober 2009)

Kommunikation und Interaktion in pädagogischen Kontexten – berufs- und wirtschaftspädagogische Perspektiven - Buer, Jürgen van; Niederhaus, Constanze (Handbuch Berufs- und Wirtschaftspädagogik)

Fachtexte in der Berufsausbildung. Ein linguistischer Vergleich von Texten aus Fachkundebüchern für die Berufsfelder Körperpflege und Elektrotechnik - Niederhaus, Constanze (Die berufsbildende Schule (62))

AlphaZ Evaluation. Sachbericht 2009 - Badel, Steffi; Niederhaus, Constanze

Basis Deutsch. Kopiervorlagen für die Berufsvorbereitung mit CD-ROM - Köhler-Knacker, Margitta; Niederhaus, Constanze; Nowak, Klaus; Wenzke, Anselm

Gezielt fördern. Verben, Präpositionen, Satzglieder, Sätze. Arbeitsheft 7./8 - Müller, Julia; Niederhaus, Constanze; Robben, Christiane

Almog, Joseph, “Frege’s Puzzles”, In: Journal of Philosophical Logic 37 (2008), 549–574 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Philosophische Tagebücher 1803–1810. Zweiter Teil", hg. v. Jan Berg (Bernard Bolzano-Gesamtausgabe. Reihe II. B.15), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2009 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Philosophische Tagebücher 1803–1810. Erster Teil", hg. v. Jan Berg (Bernard Bolzano-Gesamtausgabe. Reihe II. B.14), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2009 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

De Risi, Vincenzo, "Geometry and Monadology. Leibniz’s Analysis Situs and Philosophy of Space", Birkhäuser: Basel/Boston/Berlin 2007 (Science Networks. Historical Studies; 33) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Degen, J.W., “Variations of Frege’s Grundgesetze”, In: Travaux de logique 18 (2007), 15–31 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Yearbook of Phraseology. Hg. von Koenraad Kuiper et al (Rezensiert von Häcker, Martina) - Ptashnyk, Stefaniya

Variation und die historische Sprachkontaktforschung: Am Beispiel der multilingualen Stadt Lemberg - Ptashnyk, Stefaniya (“Variatio delectat”. Empirische Evidenzen und theoretische Passungen sprachlicher Variation. Festschrift für Klaus J. Mattheier zum 65. Geburtstag)